Produção de cachaça com grânulos de Kefir - Dornelles, Anita Saraiva (2007)
Sugar cane spirit is the most consumed alcoholic drink in Brazil. Ceará State is the 4th producer of sugar cane spirit in the country. In this way, studies regarding new alternatives to produce sugar cane spirits are very important for the local development. Sugar cane is the main raw material used in Brazil in alcoholic fermentation and the yeast Saccharomyces cerevisae is the microorganism used in industrial processes. However, other microorganisms are also able to produce ethanol using raw materials rich in sugars as substrate. In this work, the use of kefir granules in alcoholic fermentation using sugar cane as substrate is presented. Kefir granules are composed of several microorganisms entrapped in a polymeric matrix (kefiran). The main constituents of the granules are lactobacillus and yeasts (Saccharomyces, Kluyveromyces, Cândida and Pichia). These granules are traditionally used to produce fermented milk with low alcohol content. The use of such granules to produced distilled alcoholic beverages was not studied yet. A factorial planning was carried out to verify the influence of sugar concentration and the initial inocula in the ethanol yield in fermentation carried out using kefir granules an commercial baker’s yeast (Saccharomyces cerevisae). The fermented broth obtained using kefir presented higher residual sugars and lower ethanol content when compared to the fermented broth obtained using baker’s yeast. The fermented broth was distilled in a artisanal distilator (alambique). The sugar cane spirit obtained presented pleasant aroma and flavor. Physicochemical analyses of the distilled product attested their quality and conformity with the Brazilian regulations requirements considering its composition. The sugar cane spirit obtained using kefir granules was submitted to a sensory evaluation considering the product acceptance and sensory description. The spirit obtained using baker’s yeast was used as reference in the sensory evaluation of the product.